EFFECTIVE STRATEGIES FOR TEACHING AND LEARNING IN UNIVERSITY SEMINAR - DANA JUCAN (Studia Universitatis Babes-Bolyai, 2014)
ABSTRACT. In the present study we intend to identify the manner in which seminars in higher education are performed, and also the methods of teaching used during these seminars. For this purpose, we have applied a semi-structured interview to students of the Faculty of Psychology and Sciences of Education, the department for Primary and Early Years Education, numbering a total of 75 subjects. The interview comprised six questions regarding the methods of teaching used in university. For illustration, we present and analyse the answers received for four of the questions in the interview. The analysis of the answers offered by the students reveals the fact that, at the subject focused upon, interactive and applicative seminars are organised most often.